Activation of Toll-like receptor 9 inhibits LPS-induced receptor activator of NF-κB ligand expression in rat B lymphocytes - Yu, Xiaoqian (2014)
B lymphocytes express multiple Toll-like receptors (TLRs) that regulate cytokine production by these B cells. We investigated the effect of TLR4 and TLR9 activation on receptor activator of NF-κB ligand (RANKL) expression by rat spleen B cells. Splenocytes or purified spleen B cells from Rowett rats were cultured with TLR4 ligand E. coli LPS and/or TLR9 ligand CpG-oligodeoxynucleotide (CpG-ODN) for 2 days. RANKL mRNA expressions and the percentage of RANKL-positive B cells were increased in rat splenocytes challenged by E. coli LPS alone. Such increase was diminished when cells were treated with both CpG-ODN and E. coli LPS. Microarray results revealed that expressions of multiple cyclin-dependent kinase (CDK) pathway-related genes were up-regulated only in cells treated with both E. coli LPS and CpG-ODN. This study suggests that CpG-ODN inhibit LPS-induced RANKL expression in rat B cells via regulation of CDK pathway.